Proceedings of the 45th Annual Design Automation Conference 2008
DOI: 10.1145/1391469.1391680
|View full text |Cite
|
Sign up to set email alerts
|

Scan chain clustering for test power reduction

Abstract: An effective technique to save power during scan based test is to switch off unused scan chains. The results obtained with this method strongly depend on the mapping of scan flip-flops into scan chains, which determines how many chains can be deactivated per pattern. In this paper, a new method to cluster flip-flops into scan chains is presented, which minimizes the power consumption during test. It is not dependent on a test set and can improve the performance of any test power reduction technique consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Nonetheless, the difference is quite small when the rank threshold of the power-aware compression process is set to a high value. For all of the benchmarks examined, the proposed scheme delivers appreciable power reduction at the cost of a very small compression ratio loss for rank thresholds above 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the difference is quite small when the rank threshold of the power-aware compression process is set to a high value. For all of the benchmarks examined, the proposed scheme delivers appreciable power reduction at the cost of a very small compression ratio loss for rank thresholds above 19.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that uncontrolled scan power dissipation significantly degrades the scan test quality by incurring chip damage and overscreeninginduced yield loss [1]. While reducing power for non-compressed test vectors constitutes a formidable research challenge as exemplified by the number of research works published in the area [14]- [19], [29], the possibly conflicting compression goal elevates the challenge of power reduction to a highly challenging plane, as shown by the limited number of works on this topic [6], [24], [30]. The attainment of either target necessitates the appropriate utilization of the unspecified bits (don't cares) in the test cubes.…”
Section: Introductionmentioning
confidence: 99%
“…The technique in [16] focuses on the ratio of care bits in a scan chain and reduces shift power by enabling scan chains that are ineffective for detecting new faults during scan shift. To improve this technique, the approach in [17] clusters the scan chains into several groups and achieves more significant shift power reduction by limiting scan shift to a portion of groups with mask logics during scan shift. The researchers in [18,23,24] [19].…”
Section: Introductionmentioning
confidence: 99%
“…The approach in [3] clusters the scan chains into several groups and reduces shift power by enabling ineffective ones with mask logics during scan shift. Technique presented in [4] reduces test power by inserting extra logic gates to freeze the outputs of the scan flip-flops during scan operation.…”
Section: Introductionmentioning
confidence: 99%